Motion‐robust diffusion compartment imaging using simultaneous multi‐slice acquisition. Issue 5 (16th November 2018) - Marami, Bahram; Scherrer, Benoit; Khan, Shadab; Afacan, Onur; Prabhu, Sanjay P.; Sahin, Mustafa; Warfield, Simon K.; Gholipour, Ali
Abstract : Purpose: To achieve motion‐robust diffusion compartment imaging (DCI) in near continuously moving subjects based on simultaneous multi‐slice, diffusion‐weighted brain MRI. Methods: Simultaneous multi‐slice (SMS) acquisition enables fast and dense sampling of k ‐ and q ‐space. We propose to achieve motion‐robust DCI via slice‐level motion correction by exploiting the rigid coupling between simultaneously acquired slices. This coupling provides 3D coverage of the anatomy that substantially constraints the slice‐to‐volume alignment problem. This is incorporated into an explicit model of motion dynamics that handles continuous and large subject motion in robust DCI reconstruction. Results: We applied the proposed technique, called Motion Tracking based on Simultanous Multislice Registration (MT‐SMR) to multi b‐value SMS diffusion‐weighted brain MRI of healthy volunteers and motion‐corrupted scans of 20 pediatric subjects. Quantitative and qualitative evaluation based on fractional anisotropy in unidirectional fiber regions, and DCI in crossing‐fiber regions show robust reconstruction in the presence of motion. Conclusion: The proposed approach has the potential to extend routine use of SMS DCI in very challenging populations, such as young children, newborns, and non‐cooperative patients.